Prevalence and clustering of cardiovascular disease risk factors in rural Nepalese population aged 40-80 years - Mahesh Kumar Khanal; M. S. A. Mansur Ahmed; Mohammad Moniruzzaman; Palash Chandra Banik; Raja Ram Dhungana; Pratiksha Bhandari; Surya Devkota; Arun Shayami (BMC, 2018)
Abstract Background Cardiovascular diseases (CVD) are the main cause of mortality in low- and middle-income countries like Nepal. Different risk factors usually cluster and interact multiplicatively to increase the risk of developing acute cardiovascular events; however, information related to clustering of CVD risk factors is scarce in Nepal. Therefore, we aimed to determine the prevalence of CVD risk factors with a focus on their clustering pattern in a rural Nepalese population. Methods A community-based cross-sectional study was conducted among residents aged 40 to 80 years in Lamjung District of Nepal in 2014. A clustered sampling technique was used in steps. At first, four out of 18 wards were chosen at random. Then, one person per household was selected randomly (n = 388). WHO STEPS questionnaires (version 2.2) were used to collect data. Chi-square and independent t-test were used to test significance at the level of p < 0.05. Results A total 345 samples with complete data were analyzed. Smoking [24.1% (95% CI: 19.5-28.6)], harmful use of alcohol [10.7% (7.4-13.9)], insufficient intake of fruit and vegetable [72% (67.1-76.6)], low physical activity [10.1% (6.9-13.2)], overweight and obesity [59.4% (54.2-64.5)], hypertension [42.9% (37.6-48.1)], diabetes [16.2% (14.0-18.3)], and dyslipidemia [56.0% (53.0-58.7)] were common risk factors among the study population. Overall, 98.2% had at least one risk factor, while 2.0% exhibited six risk factors. Overall, more than a half (63.4%) of participants had at least three risk factors (male: 69.4%, female: 58.5%). Age [OR: 2.3 (95% CI: 1.13-4.72)] and caste/ethnicity [2.0 (95% CI: 1.28-3.43)] were significantly associated with clustering of at least three risk factors. Conclusions Cardiovascular risk factors and their clustering were common in the rural population of Nepal. Therefore, comprehensive interventions against all risk factors should be immediately planned and implemented to reduce the future burden of CVD in the rural population of Nepal.